Practices and Techniques of Jal Neti Across Indian Institutions: A Cross-sectional Study - Satya Lakshmi Komarraju; Sathyanath Dasrathan; Kajal Gupta; Shivangi Pandey; Shrikanth Muralidharan (International Journal of Yoga)
Background: Nasal irrigation, including the traditional practice of Jal Neti, is increasingly used as an adjunctive treatment for various sinonasal disorders. It enhances mucociliary clearance, reduces mucus contact with irritants, and helps alleviate sinonasal symptoms. Despite its benefits, the practices and techniques vary widely across yoga traditions, necessitating a systematic examination of these differences. Methods: This cross-sectional observational study was conducted at nine renowned yoga and naturopathy institutes in India to document and analyze the diverse practices of Jal Neti. Data were collected through direct interviews with experts, observations, and a review of institutional practices. Parameters studied included water source, purification methods, salt type and measurement, water temperature, and quality testing. Results: The study revealed significant variations in Jal Neti practices among institutions, influenced by expertise, philosophy, and environmental factors. Water sources ranged from municipal to natural sources such as dams and ground water with purification methods including reverse osmosis and chlorination. Water temperatures varied seasonally, and salt types included rock, sea, and iodized salts, with measurement techniques often subjective. The pH, total dissolved solids, and salinity levels differed, reflecting the influence of local water characteristics. Although consistent water quality testing was observed, the frequency and parameters varied, affecting practice safety and effectiveness. Conclusion: Jal Neti practices across major Indian yoga institutes exhibit significant diversity in methods, reflecting the individualistic yet systematic nature of this ancient technique. These findings highlight the need for standardized guidelines to ensure safety and efficacy, especially concerning water quality and salt concentration. The clinical relevance of these findings lies in the potential for improving the safety and effectiveness of Jal Neti for sinonasal disorders. Variations in salt types, concentrations, and water temperatures could influence mucosal irritation, symptom relief, and overall therapeutic outcomes. Standardizing these parameters could enhance the consistency and reliability, ensuring better patient outcomes in both traditional and clinical settings.